Outstanding and ordinary scientists’ co-authorship networks in the early career phase - Tang, Chaoying; Ye, Linna; Naumann, Stefanie; Lu, Xiaoyang (Malaysian Journal of Library and Information Science, 2021)
How do scientists’ ego-centered co-authorship networks affect their research productivity and impact during the early career phase? Do co-authorship networks evolve differently for outstanding scientists vs. ordinary scientists? Our study responded to these questions by demonstrating that scientists’ co-authorship network size and betweenness centrality of their co-authorship network positively affected both their research productivity and research impact. Scientists’ tie strength diversity of their co-authorship network moderated the relationship between their ego-network size and their research performance. Their co-authorship network’s degree centralization moderated the relationship between their betweenness centrality and research performance. Further, the size and betweenness centrality of the co-authorship network were significantly different between the two groups of scientists since their fourth working year. Outstanding scientists had a larger co-authorship network and their positions in the co-authorship network were more central than those of ordinary scientists. Implications for scientists and policy makers in science and higher education are discussed